2015
DOI: 10.1161/strokeaha.114.007298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Broad-Specificity Chemokine-Binding Protein on Brain Leukocyte Infiltration and Infarct Development

Abstract: Background and Purpose-Expression of numerous chemokine-related genes is increased in the brain after ischemicstroke. Here, we tested whether post-stroke administration of a chemokine-binding protein (CBP), derived from the parapoxvirus bovine papular stomatitis virus, might reduce infiltration of leukocytes into the brain and consequently limit infarct development. Methods-The binding spectrum of the CBP was evaluated in chemokine ELISAs, and binding affinity was determined using surface plasmon resonance. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…The BPSV-CBP was expressed in 293-EBNA cells as a FLAG-fusion protein and purified by affinity chromatography as described previously [21]. The purified CBP was analysed by multi-angle laser-light scattering (MALLS) (Wyatt Technology) coupled with size-exclusion chromatography (SEC) [20].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BPSV-CBP was expressed in 293-EBNA cells as a FLAG-fusion protein and purified by affinity chromatography as described previously [21]. The purified CBP was analysed by multi-angle laser-light scattering (MALLS) (Wyatt Technology) coupled with size-exclusion chromatography (SEC) [20].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of PPVs, in particular the type species orf virus (ORFV), revealed they have evolved a range of mechanisms that temporarily suppress inflammation within the infected site and delay the host’s immune response. These anti-inflammatory mechanisms include the secretion of a viral homolog of interleukin-10 that reduces the production of pro-inflammatory cytokines [916], and also secretion of a chemokine-binding protein (CBP) that impairs the chemokine network [14,1721]. In the case of BPSV, this combination of secreted viral immunomodulators in conjunction with other virulence factors may be associated with frequent subclinical infections, reinfections, and virus persistence in its natural host [6,7,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 As leukocyte activation in association with postischemic inflammation contributes to secondary brain injury, 4,5 pharmacological targeting of chemokine receptors may be an attractive means to selectively exclude immune cells that might worsen acute damage in the initial period after a stroke. 6,7 The influence of monocytes/macrophages on brain infarct development and stroke outcome is not well defined. The 2 common types of murine monocytes are classified by their level of Ly6C expression: Ly6C hi and Ly6C lo .…”
mentioning
confidence: 99%
“…The red nodes are the screened differentially expressed cytokines in our study be responsible for the migration of peripheral immune cell into the brain in neuroinflammatory conditions (Cazareth, Guyon, Heurteaux, Chabry, & Petit-Paitel, 2014). CCL2 expression is also associated with the infarct volume which plays a pivotal role in brain inflammation and infarct volume development after ischemic stroke (Lee et al, 2015). Although cytokine-cytokine receptor interaction pathway has not been fully discussed in this study, considering the important roles of these cytokines, our results imply that the above down-regulated cytokines may participate in the progression of MMI via involving in cytokine-cytokine receptor interaction pathway.…”
Section: Discussionmentioning
confidence: 65%